Transition Probability Matrix of Microcredits: The case of a Mexican microfinance - Rodríguez Vázquez, Verónica P.; Hernández Vaquero, Japhet (Estudios Económicos de El Colegio de México, 2013)
Microfinance in Mexico has developed at an accelerated pace and the efforts in credit risk management in this sector are scarce. The goal of this work is the construction of a Transition Probability Matrix in the rating of microcredits which can be used in the estimation of Value at Risk (VaR), observing the regulations of the Unique Circular of Saving and Popular Credit emitted by “Commission of National Banking and Securities” CNBV. Both, the methodology for its construction based in Markov chains theory and the obtained results, are presented. The hypotheses of absorbing state and the high recovery of microcredit are confirmed. Finally it is detected that men are as good payers as women.